Description of a new species of the Miniopterus aelleni group (Chiroptera: Miniopteridae) from upland areas of central and northern Madagascar - Goodman, Steven M.; Ramasindrazana, Beza (Zootaxa, 2015)
Recent molecular genetic work, combined with morphological comparisons, on Malagasy members of the bat genus Miniopterus (Family Miniopteridae), has uncovered a number of cryptic species. Based on recently collected specimens and associated tissues, we examine patterns of variation in M. aelleni, the holotype of which comes from Ankarana in northern Madagascar. Using molecular genetic (mitochondrial cytochrome b) and morphological characters we describe a new species, M. ambohitrensis sp. nov. In northern Madagascar, M. ambohitrensis and M. aelleni are allopatric, but occur in relatively close geographical contact (approximately 40 km direct line distance) with M. ambohitrensis found at Montagne d’Ambre in montane humid forest and M. aelleni sensu stricto at Ankarana in dry deciduous forest. Morphologically, this new taxon is differentiated from M. aelleni based on pelage coloration, external measurements, craniodental differences, and tragus shape. Comparisons using 725 bp of cytochrome b found a divergence of 1.1% within M. aelleni sensu stricto, 0.8% within M. ambohitrensis, and 3.3% between these two clades. The two sister species do not demonstrate acoustical differences based on recordings made in a flight cage. Miniopterus ambohitrensis is known from four localities in the northern and central portions of Madagascar, all from montane regions and across an elevational range from about 800 to 1600 m; its calculated “Extent of occurrence” is 15,143 km2. It is possible that this species is at least partially migratory.